Male Breast Cancer: An Analysis of Clinicopathological Features, Treatment Patterns, and Survival Outcomes over 10 Years from a Tertiary Center - Hüseyin Tepetam; Cemal Ugur Dursun; Mustafa Mert Hanilce; Solen Nasifoglu; Nursena Ciflik; Duygu Gedik; Sermin Kokten; Sule Karabulut Gul (Journal of Clinical Medicine, 2026)
Background/Objectives: Male breast cancer (MBC) is a rare malignancy accounting for less than 1% of all breast cancers, and current treatment recommendations are largely extrapolated from studies in women. We aimed to evaluate the clinicopathological characteristics, treatment patterns, survival outcomes, and prognostic factors of male breast cancer patients treated at a tertiary referral center. Methods: We retrospectively reviewed 45 patients with histopathologically confirmed MBC treated between January 2015 and July 2025. Demographic, clinicopathological, treatment, and follow-up data were collected from institutional records. Overall survival (OS) and disease-free survival (DFS) were estimated using the Kaplan–Meier method, and potential prognostic factors were analyzed using univariate Cox proportional hazards regression. Results: The median age at diagnosis was 60 years, and invasive ductal carcinoma was the predominant histological subtype (95.6%). Estrogen and progesterone receptor positivity were observed in 93.0% and 95.2% of patients, respectively, while HER2 positivity was identified in 26.8%. Modified radical mastectomy was performed in 95.6% of patients, adjuvant endocrine therapy in 88.9%, chemotherapy in 73.3%, and radiotherapy in 64.4%. After a median follow-up of 84 months (range, 1–125 months), the estimated 5-year OS and DFS rates were 85.3% and 68.4%, respectively. No locoregional recurrence was observed in the entire cohort; all recurrences were distant metastases. None of the evaluated clinicopathological variables demonstrated a statistically significant association with OS or DFS. Conclusions: This single-center experience demonstrates favorable long-term survival and no observed locoregional recurrence in a contemporary cohort of patients with male breast cancer. These real-world findings are consistent with current treatment strategies and provide additional evidence regarding the management of this rare disease. Larger multicenter collaborative studies are needed to establish robust prognostic models and generate male-specific evidence to further optimize clinical management.